A Prospective Investigation of Coffee Drinking and Bladder Cancer Incidence in the United States. Issue 5 (September 2017) - Loftfield, Erikka; Freedman, Neal D.; Inoue-Choi, Maki; Graubard, Barry I.; Sinha, Rashmi
Abstract : Background: In 1991, coffee was classified as a group 2B carcinogen, possibly carcinogenic to humans, based on limited epidemiologic evidence of a positive association with bladder cancer. In 2016, the International Agency for Research on Cancer downgraded this classification due to lack of evidence from prospective studies particularly for never smokers. Methods: Baseline coffee drinking was assessed with a food frequency questionnaire in the NIH-AARP prospective cohort study. Among 469, 047 US adults, who were cancer free at baseline, 6, 012 bladder cancer cases (5, 088 men and 924 women) were identified during >6.3 million person-years of follow-up. Multivariable-adjusted Cox proportional hazards models were used to estimate hazard ratios (HR) and 95% confidence intervals (CI), with non-coffee drinkers as the reference group. Results: Coffee drinking was positively associated with bladder cancer in models adjusted for age and sex (HR for ≥4 cups/d relative to coffee nondrinkers = 1.91, 95% CI = 1.70, 2.14; P trend < 0.0001). However, the association was substantially attenuated after adjustment for cigarette smoking and other potential confounders (HR for ≥4 cups/d relative to coffee nondrinkers = 1.18, 95% CI = 1.05, 1.33; P trend = 0.0007). Associations were further attenuated after additional adjustment for lifetime smoking patterns among the majority of the cohort with this available data ( P trend = 0.16). There was no evidence of an association among never smokers ( P trend = 0.84). Conclusions: Positive associations between coffee drinking and bladder cancer among ever smokers but not never smokers suggest that residual confounding from imperfect measurement of smoking or unmeasured risk factors may be an explanation for our positive findings. Abstract : Supplemental Digital Content is available in the text.